APRESIASI WARGA DUSUN KARANGTENGAH KIDUL MELALUI MUSIK ANSAMBEL DALAM PERSPEKTIF NILAI MAX SCHELER - Annas Fitria Sa’adah (Sanjiwani: Jurnal Filsafat, 2025)
An ensemble is a group playing musical instruments. Playing music as an ensemble is useful for practicing teamwork to put on a good performance. One of the musical ensemble activities was carried out by residents of Karangtengah Kidul in Yogyakarta. This ensemble activity was held specifically in celebration of Indonesia's independence day, where this routine activity is carried out by the residents of Karangtengah Kidul as a cultural Carnival Village every year in August. The aim of this research is to analyze the musical ensemble activities carried out by the residents of Karangtengah Kidul with the perspective of Max Scheler's values. The researcher made observations and observations regarding the readiness of residents or ensemble players, trainers, and the musical equipment used, arranging songs and performing them. This research is qualitative research which begins with observations, then interviews and documentation. The results of this research are based on Max Scheler's value perspective that the innovation and creation of musical ensemble performances by the residents of Karangtengah Kidul in the Cultural Carnival event contain enjoyment and vitalist values, so it can be concluded that by participating in this ensemble music game it is able to bring happiness and satisfaction to the players. who come from various age groups.